Dampak Perambahan Hutan Taman Nasional Lore Lindu Terhadap Fungsi Hidrologi Dan Beban Erosi (Studi Kasus Daerah Aliran Sungai Nopu Hulu, Sulawesi Tengah) - Yayat Hidayat; Naik Sinukaban; Hidayat Pawitan; Suria Darma Tarigan (Institut Pertanian Bogor, 2007)
The research was proposed to identify rainforest conversion impact on hydrologic function and soil erosion, and its simulation using ANSWERS model. Surface runoff and soil erosion were measured in soil erosion plots and outlet of Nopu Upper Catchment. Rainforest conversion to agricultural lands were significantly increased soil erosions and surface runoffs. Soil erosion from maize and peanut rotation was higher 2061.8% than natural forest. It higher value also in intercroping young age cocoa, maize and cassava and maize were 2023.8% and 2012.3% respectively. While surface runoffs increased up to 761.7°/o on bare plot, 567.5% on medium age cocoa, 446.8°/o on young age cocoa, 415.1°/o on intercroping young age cacao, maize and cassavas, 405.9°/o on old cocoa, and 329.5% on intercroping young age cacao and cassavas. Crop and management factor (C factor) value is significantly corelated with outputs of ANSWERS model. Using daily daily C factors, the ANSWERS model performs well in predicting soil erosion which is showed by determination coefficent (Jr = 0.89), model efficiency (0.86), and average of percentage model deviations (24.1%). Whereas using USlE C factor, model accuracy lower which represented by model coefficient (0.40) and average of percentage model deviations (63.6%). Using daily C factors, ANSWERS model simulation indicates rainforest conversion into agricultural lands on Nopu Upper Catchment has caused soil and water loss 3190.5 ton/year and 115441.0 m3/year, respectively. Agroforestry system practices in agricultural lands which in line with reforestation in stream line and steep agricultural areas (slope> 40°/o) was effective to reduce soil erosions up to 77.6°/o.